Konten Review dan Kredibilitas Sutradara Terhadap Keputusan Menonton Film ‘Petualangan Sherina 2’ - Destri Sari Gunarti; Lasmery RM Girsang; Ilona VO Situmeang; Nugroho Adi Susilo; Andis Samiaji (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Nowadays, the development of the film industry in Indonesia is accelerating. The progress of the local/national film industry, in particular, is unstoppable, driven by technological advancements. For example, the emergence of YouTube as a platform has made it easier for film enthusiasts to enjoy film-related content. Film producers and marketers are increasingly motivated to compete in promoting and marketing their film content. In this context, audiences are becoming more inclined to watch film programs. However, amid the growing number of national film productions, there is one genre that remains relatively underproduced. The release of a children’s/teen musical film, first introduced through ‘Petualangan Sherina’, which competes with other film genres, can create uncertainty. The problems identified by the author stem from several factors such as content, the director, and the decision to watch a film. Thus, this article focuses on three variables: variable X1 (Review Content), variable X2 (Director Credibility), and variable Y (Viewing Decision), which will be further examined by the Social Judgment Theory. The purpose of this study is to determine the magnitude of the influence of all these variables. The research design employs a positivist paradigm, a quantitative approach, an explanatory nature, and a survey method. The results, based on correlation test data analysis, show a strong relationship between the “Review Content” variable and “Viewing Decision,” as well as a strong relationship between “Director Credibility” and “Viewing Decision.” Meanwhile, the multiple correlation test indicates that simultaneously, “Review Content” and “Director Credibility” have a moderately strong relationship with “Viewing Decision.” Furthermore, the F-test results reveal a positive and significant influence of both “Review Content” and “Director Credibility” on the “Viewing Decision.